Burden and Trends of Severe Rotavirus Infections and Allcause Acute Gastroenteritis Hospital Episodes in Children Under Five Years Old in Mainland Portugal - Héloïse Lucaccioni; Rita Sá Machado (Acta Médica Portuguesa, 2021)
Introduction: Rotavirus infections are a leading cause of severe acute gastroenteritis in children under five years old. In December 2019, Portugal announced the inclusion of the rotavirus vaccine, already available for private purchase, in the National Immunization Program. We present the first nationwide analysis of the burden and trends of rotavirus and acute gastroenteritis hospital episodes in children under five years old in mainland Portugal (2014 - 2017). Material and Methods: We used the hospital morbidity database and the Death Certificate Information System to identify hospital episodes and deaths of rotavirus and acute gastroenteritis based on the codes of the International Classification of Diseases. We described the number and rates of hospital episodes disaggregated by age group, sex, geographical units, and the seasonality and trends over the study period. Results: On average, during the study period, there were 1985 annual hospital episodes among children under five years old. The annual rate was 48.0/10 000 children (95% CI 46.9 - 49.0). Rates were consistently higher in younger children, and 67.8% episodes occurred in children under 24 months. We found a seasonal pattern with a major peak in the early spring. Discussion: Our results were consistent with the current knowledge on rotavirus and acute gastroenteritis hospital episodes in Europe. Additional studies are needed to identify the risk factors and high-risk groups for hospital attendance. Conclusion: Rotavirus and acute gastroenteritis hospital episodes in children under five years old in mainland Portugal represent an important health and economic burden. In the future, monitoring this burden and these trends in relation with rotavirus vaccine coverage could be useful in order to assess the impact of the vaccination programme on the change in hospital episodes.